2021
DOI: 10.1075/ssol.21012.kos
|View full text |Cite
|
Sign up to set email alerts
|

Reading fiction with an e-book or in print

Abstract: Empirical research on the differences between digital and print reading has recently increased, mainly concentrating on informational texts while disregarding literary texts. Concerning narrative fiction, the existing quantitative studies have found no or very few differences between reading printed books and e-books. In our focus group study, we amplify the perspective on digital and print book reading through a largely explorative approach. The results gained by interviewing 34 habitual readers of e-books in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…Nevertheless, for multi-format users, print is still the preferred reading medium for most genres. However, we were not able to replicate our focus group findings which stated that crime novels, thrillers, and other light fiction were preferably read digitally (Kosch et al, 2021). The survey showed that there is no preference for a reading medium when reading romance and entertainment novels or crime, thriller, and horror.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, for multi-format users, print is still the preferred reading medium for most genres. However, we were not able to replicate our focus group findings which stated that crime novels, thrillers, and other light fiction were preferably read digitally (Kosch et al, 2021). The survey showed that there is no preference for a reading medium when reading romance and entertainment novels or crime, thriller, and horror.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, the questionnaire consisted of questions probing how many books participants read on average per year and how many minutes they read on average per week. Based on a focus group study (Kosch et al, 2021), we used a self-developed scale with nine items with a 4-point Likert scale exploring reading motivation. To create the subfactors of the reading motivation scale, we conducted an exploratory maximum likelihood factor analysis with varimax rotation, creating three distinct subfactors: escapism (Cronbach's α = .66), education (Cronbach's α = .72), and culture (Cronbach's α = .65).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations